Evaluation of corporate initiatives in ergonomics: Effectiveness of ergonomics training in an oil and gas refinery company - Taha, Z.; Muhammad, M.Z. (2009)
Corporate initiatives in ergonomics refer to the initiatives taken by corporation to introduce and implement ergonomics program. It is highly desirable in order to achieve optimum performance of productivity and a quality of working life, especially in the increasing competitive global market where the survival of a corporation depends on how it responds to a highly dynamic and complex environment. Somehow, implementing corporate initiatives in ergonomics will not be easy. Therefore, the objective of this paper is to examine the correlation between corporate initiatives towards ergonomics and ergonomics training effectiveness. A Sociotechnical System (STS) as an open system approach on how to design work and its environment which integrates engineering and social science is used to conduct this study. Four elements of STS components: the technological subsystem, the personnel subsystem, the relevant environments and organizational structure is studied by quantitative and quailitative methods. The finding of this study shows that the top management initiated an ergonomics program due to strong request from employees. An external consultant was hired to solve ergonomics problem raised by the workers and train members on ergonomics. The ergonomics training program was found to be an important and effective approach in introducing ergonomics. Somehow, in order to ensure that ergonomics have great impact on the overall company's performance, ergonomics training need to be designed and tailored according to the target audiences and needs.